2005
DOI: 10.1055/s-2005-837760
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Xanthones from Guttiferae Plants on PAF-Induced Hypotension in Mice

Abstract: The inhibitory effects of 22 xanthones from three Guttiferae plants (Hypericum patulum, Calophyllum inophyllum and C. austroindium) on exogenous platelet activating factor (PAF)-induced hypotension were examined using a blood pressure monitoring in vivo assay method. Guanandin (2), caloxanthone E (3), 1,3,5,6-tetrahydroxy-2-isoprenylxanthone (8), 6-deoxyjacareubin (11) and patulone (18) showed strong inhibition of PAF-induced hypotension, with inhibitory effects of more than 60 %. Their ID50 values were greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Many members of this group contain compounds that have already been identified, such as lignans and sesquiterpenes from burdock, xanthones from hidcote [23], flavonoids from garcinia [24], and the widely reported ginkgolide B from ginkgo [25].…”
Section: Paf Inhibitorsmentioning
confidence: 99%
“…Many members of this group contain compounds that have already been identified, such as lignans and sesquiterpenes from burdock, xanthones from hidcote [23], flavonoids from garcinia [24], and the widely reported ginkgolide B from ginkgo [25].…”
Section: Paf Inhibitorsmentioning
confidence: 99%
“…Xanthones isolated form C. inophyllum exhibited in vivo anti-inflammatory activity when administered through intraperitoneal or oral routes in rats (Gopalakrishnan et al 1980). Oku et al (2005) studied inhibitory effects of 22 xanthones on exogenous plateletactivating factor (PAF)-induced hypotension in in vivo assay. The result of the study showed that caloxanthone E, 1,3,5,6-tetrahydroxy-2-isoprenylxanthone, 6-deoxyjacareubin and guanidine showed 60% inhibition in PAF-induced hypotension (Oku et al 2005).…”
Section: Antioxidant Activity and Anti-inflammatory Activitymentioning
confidence: 99%
“…Various constituents of H. ascyron have been reported to date, and flavonoids [3][4][5][6] and xanthones [7] have been confirmed as components of this plant. The family Clusiaceae is a known rich source of xanthones [8,9], which have been shown to have various bioactivities, including those of anti-methicillin-resistant Staphylococcus aureus (MRSA) [10][11][12], anti-vancomycin-resistant Enterococci (VRE) [13], anti-malarial [14], tumor-promoting inhibition [15], selective cyclooxygenase-2 inhibition [16], and inhibitory effects on platelet-activating factor (PA-F)-induced hypotension [17]. In the course of our search for bioactive natural products from plants, we became interested in Hypericum plants and their chemical constituents.…”
Section: Introductionmentioning
confidence: 99%